Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{1}{3}+\frac{6}{11}.\frac{22}{5}-\frac{3}{4}:1,5=\frac{1}{3}+\frac{6.2}{5}-\frac{3}{4}:\frac{3}{2}=\frac{1}{3}+\frac{12}{5}-\frac{1}{2}=\frac{10}{30}+\frac{72}{5}-\frac{15}{30}=\frac{67}{30}\)
\(b, 3.3,5.6+2.6,4.9+1,8=18.3,5+18.6,4+1,8=18\left(3,5+6,4\right)+1,8=18.9,9+1,8=1,8.99+1,8=1,8\left(1+99\right)=1,8.100=180\)
b ) 3 x 3,5 x 6 + 2 x 6,4 x 9 + 1,8
= 18 x 3,5 + 18x 6,4 + 18 x 0,1
= 18 ( 3,5 + 6,4 + 0,1)
= 18 x 10
= 180
b) \(\Leftrightarrow18x-288=27.4+8.9-144\)
\(\Leftrightarrow18x=108+72-144+288=324\)
\(\Leftrightarrow x=18\)
Bài làm
a) x² - 3 = 22
=> x² = 25
=> x = + 5
Vậy x = + 5
b) 2x³ + 5 = -11
2x³ = -16
x³ = -8
x = -2
Vậy x = -2
c) ( x + 2 )² = 81
=> x + 2 = 9
=> x = 7
Vậy x = 7
d) ( 2x + 1 )² = 25
=> 2x + 1 = 5
=> 2x = 4
=> x = 2
Vậy x = 2
e) 5x + 2 = 625
5x = 623 ( vô lí )
g) ( 2x - 3 )² = 36.
=> 2x - 3 = 6
=> 2x = 9
=> x = 4,5
Vậy x = 4,5
h) ( 2x - 1 )³ = -8
=> 2x - 1 = -2
=> 2x = -1
=> x = -1/2
Vậy x = -1/2
i) ( x - 1 )x + 2 = ( x - 1 )x + 6
=> [ (x - 1 )x - ( x - 1 )x ] = 6 - 2
=> 0 = 4 ( vô lí )
Vậy x thuộc rỗng.
k) x² + x = 0
=> x( x + 1 ) = 0
=> x = 0 hoặc x + 1 = 0
=> x = 0 hoặc x = -1
Vậy x = 0 hoặc x = -1
(2x - 7) + 17 = 6
=> 2x - 7 = 6 - 17
=> 2x - 7 = -11
=> 2x = -11 + 7
=> 2x = -4
=> x = -4 : 2
=> x = -2
+) 12 -2(3 - 3x)= -2
=> 2(3 - 3x) = 12 + 2
=> 2(3 - 3x) = 14
=> 3 - 3x = 14 : 2
=> 3 - 3x = 7
=> 3x = 3 - 7
=> 3x = -4
=> x = -4/3
\(\left(x+1\right)\left(x-3\right)=0\)
=> \(\orbr{\begin{cases}x+1=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-1\\x=3\end{cases}}\)
Vậy...
[ là dấu giá trị tuyệt đối?
2[x+3]+6=22
=> 2[x+3] = 22 - 6
=> 2[x+3] = 16
=> [x+3] = 16 : 2
[x + 3] = 8
=> x + 3 = 8 hoặc x + 3 = -8
+) Nếu x + 3 = 8 => x = 8 - 3 = 5
+) Nếu x + 3 = -8 => x = -8 - 3 = -11
Vậy x = 5; -11